Personal computers in the Business Science Department at the library. - Unknown (Forsyth County Public Library, 1990)
Photo made in the 1990s.
Personal computers in the Business Science Department at the library.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Forsyth County Public Library; Winston-Salem (N.C.)